Networked Emotional News on Social Media. (20th October 2020) - Al-Rawi, Ahmed
ABSTRACT: This paper examines news and emotions by studying Facebook Reactions (emojis) that were introduced in February 2016. Four main emotions are investigated by exploring readers' reactions to news stories selected from a sample of over 12, 000 news items posted on the English language Facebook pages of CNN, ABC News, BBC, and Sky News in 2016. There is little empirical research on the emotional aspect of news consumption on social media, and this study proposes the concept of networked emotional news and links it to research on emotions and the theory of news values. The findings indicate that social media readers are emotionally engaged with news that involves positive feelings especially love if one takes into account the top news stories as well as the total number of emoji clicks for the top 10 stories, while negative news that involves sad feelings remain the most dominant if the overall frequency of such stories is taken into account.